Triglyceride Is a Useful Surrogate Marker for Insulin Resistance in Korean Women with Polycystic Ovary Syndrome - Park, So Yun (Yonsei Med J, 2015)
PURPOSE: To evaluate lipid profiles and liver enzymes as surrogate markers used for recognizing insulin resistance in Korean women with polycystic ovary syndrome (PCOS). MATERIALS AND METHODS: 458 women with PCOS were divided into two groups: non-obese with a body mass index (BMI)<25.0 kg/m(2) and obese with a BMI≥25.0 kg/m(2). Anthropometric measures and blood sampling for hormone assay, liver enzymes, lipid profiles and 75 g oral glucose tolerance test were performed. Insulin resistance was defined as homeostasis model assessment of insulin resistance (HOMA-IR)≥2.5. Areas under the receiver operating characteristic (ROC) curves were used to compare the power of serum markers. Multiple linear regression analysis was used to evaluate the contribution of each confounding factor for HOMA-IR. RESULTS: In non-obese and obese groups, the ROC curve analyses demonstrated that the best marker for insulin resistance was triglyceride (TG), with the areas under the ROC curve of 0.617 and 0.837, respectively. Low-density lipoprotein cholesterol (LDL-C) was the significant marker for insulin resistance with areas under the ROC curve of 0.698 in obese group, but not significant in non-obese group. TG and LDL-C were significantly associated with HOMA-IR in both non-obese and obese PCOS women by multiple linear regression analysis. The optimal cut-off points of TG≥68.5 was a marker for predicting insulin resistance in non-obese PCOS patients and TG≥100.5 in obese group. CONCLUSION: TG can be used as a useful marker for insulin resistance in Korean women with PCOS, especially for obese patients.